Co-simulation for real time safety verification of nuclear power plants - Emmanuel BOAFO (The Japan Society of Mechanical Engineers, 2017)
Small and major accidents and near misses are still occurring in nuclear power plants (NPPs). Risk level has increased with the degradation of NPP equipment and instrumentation. In order to achieve NPP safety, it is important to continuously evaluate risk for all potential hazard and fault propagation scenarios and map protection layers to fault / failure / hazard propagation scenarios to be able to evaluate and verify safety level during NPP operation. There are major limitations in current real time safety verification tools, as it is mainly offline and with no integration to NPP simulation tools. The main goal of this research is to develop real time safety verification with co-simulation tool to be integrated with plant operation support systems. This includes the development of static and dynamic fault semantic network (FSN) to model possible fault propagation scenarios and the interrelationships among associated process variables. The detailed methodology involves the integration of process models, construction of static FSN with fault propagation scenarios, and evaluation and tuning of dynamic FSN with probabilistic and process variable interaction values. The focus however of the present study is to highlight the need to incorporate error reduction in performing safety verification of NPPs. Two selected case studies were used to demonstrate the proposed methodology; one on a turbine trip and the other on steam generator tube rupture. In the former case, the error reduction concept was shown while the safety verification method was demonstrated in the latter case. The results confirmed the importance of error reduction as well as the need to constantly undertake safety verification of safety critical systems such as a NPP.